FEATURES OF WORKING WITH YOUTH IN THE EDUCATION SYSTEM - Sultonova , Latofat Sa’dullaevna (Educational Research in Universal Sciences, 2023)
In this article, no matter how much we appreciate the positive role of globalization in turning the achievements in the field of science, technology, and technology into the property of the peoples of the world, we cannot ignore the fact that inequality is emerging in this process. It was analyzed that the development of the country directly depends not only on the intelligence, knowledge and skills of the young generation of hardworking citizens, but also on their health and physical fitness.